O consumidor de frutas frescas da cidade de Lavras - MG - Gonçalves, Jorge Ricardo de Almeida (1998)
In this work, a marketing research with the purpose ofidentifying the fresh fruit consumeis profile ofthe city ofLavras-MG, Brazil was developed. A set of variables related to the consumer and purchase habits, to the product evaluative criteria and purchase spots and to the consumers' demographic profile was taken into consideration. The study was conducted in two steps: an exploratory, held inthe period ofSeptember 17 toNovember 1,1997 made up of 7 semi-structured interviews and whose data were submitted to qualitative analysis the other descriptive, carried out in the period ofJanuary 6 to February 12, 1998, which consisted of 192 structured interviews, established from a stratifiedsamplingby family income and whosedata were submitted to statistical analysis. The results showed in a general way, a little diversified consumption based upon banana, orange, papaya, apple and lemon, being the fruits consumed chiefly in natura andat any time of the day. The housewife was identified as the leading responsible for the purchase activities which were done weekly, specially in supermarkets or specialized shops and preferably on the days which new products arrived and at the same occasion ofthe purchase ofvegetables. Hygiene and cleanliness, the fresh products and ofquality, price and attendance composed the main evaluative criteria in relation to the purchase spots. On the other side, the quality ofthe fruits (stood for by the features: appearance, texture, freshness and flavor) and price made up the most relevant criteria concerning with the products at the moment of purchase. In compensation, it was found that the criteria nutritive value, safety and origin ofproducts tend to be more utilized as the consumers acquire information or personnel knowledge that inable them to distinguish the products according to these features. But the trademarks or packages did not constitute representative evaluative criteria, there being a disinformation ofthe consumer as tomotives related to the presence ofstamps or labels as well as resistence to buying wrapped fruits. As for demography, the influence ofthe variable family income in expenditures on fruits, diversifícation ofthe consumption and evaluative criteria, concluding that it presents itselfas an alternative for marketing segmentation strategies.